Optical polarimetry of infrared excess stars - Chavero, Carolina Andrea (2006)
We present UBRVI polarimetry measurements for a group of 38 IRAS infrared excess stars and complement these observations with V-band data taken from the literature for 87 additional objects. After correcting the observed values by the interstellar contribution, we find that 48% of the analyzed sample has polarization excess. In addition, the polarization of these stars may correlate with infrared color excesses, particularly at 60 and 100 μm. We caution, however, that poor IRAS data quality at longer wavelengths affects this correlation. We analyze the wavelength dependence of the linear polarization of 15 polarized objects in relation to Serkowski´s empirical interstellar law. We find that for 6 to 7 objects (depending on the interstellar model) the measured polarization differs significantly from the empirical interstellar law, suggesting an intrinsic origin. We analyze the polarimetry distribution of IRAS infrared excess objects in relation to the Exoplanet host stars (i.e., stars associated with at least one likely planetary mass object). The corresponding polarimetry distributions are different within a high confidence level. Finally, we compare the metallicity distributions of F and G IRAS infrared excess, Exoplanet host and field main sequence stars, and find that F-G IRAS infrared excess objects have metallicities quite similar (although not identical) to field main sequence stars and significantly different from the Exoplanet host group.